Working time and rest - Lytvynenko, Maria; Vlasenko, Ludmila (My University, 2014)
Working time is a common measure of the amount of labor. The total working time is determined, on the one hand, by the level of production, on the other is by the physical and physiological features of human. Improved use of time is one of the main ways to increase productivity. In the analysis of working time and the state of labor discipline in the enterprise must take into account the conditions of the enterprises.
Keywords: productivity; level of production; working time; продуктивність; рівень виробництва; робочий час; производительность; уровень производства; рабочее время; кафедра ділової іноземної мови та міжнародної комунікації